Novel mutant camelina and jatropha as valuable feedstocks for biodiesel production - Muhammad Mahran Aslam (Nature Portfolio, 2020)
Abstract Novel mutant camelina has become a crop of interest inspired by its short growing season, low harvesting costs and high oil composition. Despite those advantages, limited research has been done on novel mutant lines to determine applicability for biodiesel production. Jatropha is an extremely hardy, frugal and high oil yielding plant species. The major aim of the present study was not only to compare biodiesel production from jatropha and camelina but was also to test the efficacy of camelina mutant lines (M6 progenies) as superior feedstock. The biodiesel yield from camelina oil and jatropha oil was 96% and 92%, respectively. The gas chromatographic analysis using flame ionization detector (GC-FID) showed that mutant camelina oil biodiesel sample contain major amount of oleic acid (46.54 wt%) followed by linolenic acid (20.41 wt%) and linoleic acid (16.55 wt%). Jatropha biodiesel found to contain major amount of oleic acid (45.03 wt%) followed by linoleic acid (25.07 wt%) and palmitic acid (19.31 wt%). The fuel properties of produced biodiesel were found in good agreement with EN14214 and ASTM D6751 standards. The mutant camelina lines biodiesel have shown comparatively better fuel properties than jatropha. It has shown low saponification value (120.87–149.35), high iodine value (130.2–157.9) and better cetane number (48.53–59.35) compared to jatropha biodiesel which have high saponification value (177.39–198.9), low iodine value (109.7–123.1) and lesser cetane number (47.76–51.26). The results of the present student of utilizing novel mutant camelina lines for biodiesel production are quite promising and are helpful in turning out the outcomes of the previous studies suggesting that C. sativa biodiesel presents serious drawbacks for biodiesel applications.